The wife upstairs - McFadden, Freida ([Freida McFadden], 2020)
Victoria Barnett has it all. A great career. A handsome and loving husband. A beautiful home in the suburbs and a plan to fill it with children. Life is perfect -- or so it seems. Then she's in a terrible accident... and everything falls apart. Now Victoria is unalbe to walk. She can't feed or dress herself. She can't even speak. She is confined to the top floor of her house with twenty-four-hour care. Sylvia Robinson is hired by Victoria's husband to help care for her. But it turns out Victoria isn't as impaired as Sylvia was led to believe. There's a story Victoria desperately wants to tell... if only she can get out the words. Then Sylvia discovers Victoria's diary hidden away in a drawer. And what's inside is shocking.--Back cover.